Dataset on physicochemical properties of particle-sized moringa oleifera seed cake and its application as bio-coagulants in water treatment application - Zaid, Aziz Qannaf; Suriati, Ghazali (Elsevier, 2019)
The dataset provided information about on the phytochemical and mineral composition of investigation Moringa oleifera cake residue used for the bio-coagulation of water for drinking. Four sets of mass spectrometric methods viz; Gas Chromatography Mass- Spectrometer (GC–MS), Fourier transform infrared (FTIR), LC-MS-Quadrupled time of Flight Mass Spectrometer (LC-MS/QToF), X-ray fluorescence analysis (XRF). The three spectrometry approaches provided a blueprint and basis for future investigation on the physicochemical properties of Moringa oleifera in an eco-friendly water treatment process.